The Effect of 3-Liver Pressure Point on Postpartum Severity of Pain: randomized clinical trial - Mahdieh Abouei Mehrizi; Reza Heshmat; Parisa Reza Nezhad; Malihe Nasiri; Afsar Tabatabaie Bafghi; Atiyeh Javaheri; Giti Ozgoli (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2020)
Introduction: Controlling postpartum pain affects maternal care of baby and mother's return to normal life. Studies have shown the effect of pressure on the 3- liver point in reducing uterine-induced pain, such as menstrual pain. Therefore, this study was performed with aim to evaluate the effect of 3-liver pressure point on postpartum severity of pain. Methods: This controlled randomized clinical trial study was performed on 150 mothers who had normal delivery and complained of postpartum pain in the postpartum ward of Shahid Sadoughi Hospital in Yazd in 2017-2018. Mothers were randomly divided into three groups of 3-liver pressure point (n=50), Sham group (n=50) and Ibuprofen group (n=50). All three groups received oral Ibuprofen 400 mg every 6 hours up to 24 hours if they had moderate or severe pain. In the 3-liver pressure point group (intervention group), the pressure was applied to the 3-liver point for 10 minutes on each foot, and in the Sham group, the same pressure was applied to the ectopic point. The Control group received medication only (routine care). Pain was measured every 6 hours before, 30 and 120 minutes after each intervention. Data analysis was performed using SPSS software (version 16) and tests of Chi-square, Friedman, Kruskal Wallis, Wilcoxon, and GEE)Generalized Estimation Equations (. P<0.05 was considered statistically significant. Results: The postpartum pain severity after the intervention were statistically significantly different in each group (p <0.001). The mean of postpartum pain severity decreased as 0.34 over time. The mean pain score in the 3-liver point group was 0.8±0.23 lower than the control group (p=0.001). The mean pain score in the 3-liver point group was 0.0±64.3 lower than the sham group (p = 0.035). But there was no significant difference between the sham and control groups (p = 0.468). Conclusion: Acupressure at 3-liver point is effective in relieving postpartum pain and it can be used like other pressure points affecting postpartum pain.